Around the world in 80 days - Verne, Jules (New York : Baronet Books, 1989)
In 1872 Phileas Fogg wins a bet by traveling around the world in seventy-nine days, twenty-three hours, and fifty-seven minutes.
Keywords: Voyages around the world -- Juvenile fiction; Adventure stories; Voyages around the world